2023
DOI: 10.3390/bs13080686
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Abbreviated Scale of the CENVI Questionnaire to Evaluate the Perception of School Violence and Coexistence Management of Chilean Students: Differences between Pandemic and Post-Pandemic

Flavio Muñoz-Troncoso,
Isabel Cuadrado-Gordillo,
Enrique Riquelme-Mella
et al.

Abstract: The objective of the study was to specify an abbreviated model of the school coexistence questionnaire for non-violence (CENVI) for students from 5th to 8th grade (9 to 14 years old), in order to determine the perception of violence and management of school coexistence, and the differences between Mapuche and non-Mapuche students. A total of 1870 students from schools in the city of Temuco (Chile) responded to the CENVI questionnaire. There were two samples: (1) Pandemic, with online, face-to-face and hybrid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…It also corroborates the importance of training tools that facilitate the management of coexistence and the approach to situations of violence (Morales et al, 2014). It is important to note that this result is opposite to that reported by Muñoz-Troncoso et al (2023b), where a null effect of management on violence was found. However, this effect can be explained by the fact that the questionnaire used in that study measures the perception of students, actors who, according to López et al (2023), have little or no impact on coexistence management.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…It also corroborates the importance of training tools that facilitate the management of coexistence and the approach to situations of violence (Morales et al, 2014). It is important to note that this result is opposite to that reported by Muñoz-Troncoso et al (2023b), where a null effect of management on violence was found. However, this effect can be explained by the fact that the questionnaire used in that study measures the perception of students, actors who, according to López et al (2023), have little or no impact on coexistence management.…”
Section: Discussioncontrasting
confidence: 99%
“…Having a psychometrically developed questionnaire such as the one presented is relevant for understanding the phenomenon of violence in schools and for the analysis of coexistence management. A comprehensive perspective in this regard can favor decision-making (Torrego et al, 2022) to prevent and mitigate the effects of violence (Muñoz-Troncoso et al, 2023b). Thus, the novelty of the study is the development of a psychometric scale-for teachers-that incorporates factors of mutual violence between students and teachers, in addition to the factor of school coexistence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations